From Faith to Firmness: Islamic Literacy, Ecosophy, and Management in Building Sustainable SMEs - Haanurat, A. Ifayani (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study investigates the interplay of Islamic literacy and Islamic ecosophy in shaping business sustainability among 250 Muslim SME vendors, with Islamic management positioned as a mediating mechanism. As we embed religiously grounded constructs into a structural model, the research advances marketing scholarship with a novel integration of Islamic epistemologies and sustainability-oriented management practices. Using PLS-SEM, the results demonstrate that Islamic literacy directly enhances both Islamic management and business sustainability, while Islamic ecosophy contributes significantly through its effect on management practices. Islamic management itself emerges as a critical pathway translating Islamic values into sustainable business outcomes. These findings extend theoretical debates on faith-driven management by demonstrating the mediating logic of Islamic managerial conduct. The study provides practical implications for SME owners and policymakers, highlighting how nurturing Islamic literacy and managerial ethos can strengthen operational practices and advance long-term sustainability in competitive markets.